Two pedigrees with arrhythmogenic right ventricular cardiomyopathy linked with R49H and F531C mutation in DSG2 - Chen, Xuepin (Hum Genome Var, 2019)
Arrhythmogenic right ventricular cardiomyopathy (ARVC) presents as the progressive fibrofatty replacement of the cardiomyocytes particularly in the right ventricular wall. Here, we report two cases with ARVC. In family A, the proband carries a Desmoglein2 (DSG2) gene complex heterozygous mutation NM_001943.4:c.146G>A/p.(Arg49His)and NM_001943.3:c.1592T>G/p.(Phe531Cys). In family B, the proband carries a homozygous mutation NM_001943.3:c.1592T>G/p.(Phe531Cys).